Modern Techniques of Radiation Therapy in the Treatment of Brain Tumors and Tumors of the Skull Base Moderne Verfahren für die Strahlentherapie von Hirntumoren und Tumoren der Schädelbasis - Diehl, Christian D.; Combs, Stephanie E. (Aktuelle Neurologie, 2018)
Today the choice of radiation oncology technique and treatment concept is highly individualized. Modern techniques enable high local dose depositions with significant sparing of normal tissue. This has significantly improved the therapeutic window. Molecular markers guide therapy decisions within the interdisciplinary context, for primary as well as secondary brain tumors. Skull base tumors profit from highly precise radiation techniques; often, radiotherapy can be seen as a treatment alternative to surgery in this region.
CRIS-Team Scopus Importer:2023-03-08
Keywords: brain metastases; gliomas; intensity modulated radiation therapy/IMRT; skull base tumors; stereotaxy